Pemberdayaan Edupreneurship dan Life Skill Membatik di SD Supriyadi Semarang - Setiyono, Yuuki Chleo Pratama (Pena Edukasia, 2023)
This study aims to describe the model for organizing the empowerment of batik arts at SD Supriyadi Semarang. The research subjects were school administrators, assistants and facilitators in empowering the batik life skills. Data collection was carried out in stages according to what the researchers needed. The techniques used are observation, interviews and documentation. The stages of data analysis in this study are data reduction, data presentation and conclusion. Data reduction is meant by summarizing data, choose the main things, arranged systematically. Presentation of data aims to make it easier for researchers to understand the research results that have been obtained. Source triangulation was carried out to explain the validity of the data with various sources in finding the required information. The implementation of the SDN batik life skills empowerment program in Pandak District was carried out through several stages, namely: (1) Developing a strategic plan for batik life skills education and training through empowerment for schools that were the object and subject of the training. (2) Compile: a) batik curriculum for elementary school students, b) batik competency standards, c) indicators of competency achievement in batik and teaching batik for teachers, d) develop indicators of competency achievement in batik for elementary school students. (3) Providing experienced instructors to support empowerment activities.